Ethics briefings - Chrispin, E. (Journal of medical ethics, 2009)
In July 2009, the House of Lords ruled that the Director of Public Prosecutions (DPP) must produce clear guidelines on the prosecution of those who help friends or relatives travel abroad for assisted suicide.1 As previously reported here, both the High Court and Court of Appeal had rejected Debbie Purdy’s case before it reached the Lords.2 As a person with primary progressive multiple sclerosis, she had asked the court to rule that her husband would not face prosecution if he accompanied her to Switzerland if she decides to end her life.3By requiring the DPP to publish offence-specific guidelines about the circumstances in which a prosecution would be brought, the law lords did not go so far as to assert a right to assistance in dying by legalising assisted suicide. It was reiterated that any change to the criminal law against aiding and abetting suicide remained a political matter for Parliament. The Lords did, however, acknowledge that the right to privacy, and the associated right to autonomy, was potentially infringed by the absence of a transparent policy about those who are competent and terminally ill, or severely and incurably disabled, and who need help to travel abroad for assisted dying. The five law lords unanimously agreed that Ms Purdy’s right to a private life, as protected by article 8 of the European Convention on Human Rights, included the right to clarity regarding the exercise of the DPP’s discretion as to whether or not to prosecute.Following the Lords’ ruling, the DPP, Keir Starmer, confirmed that the new guidance would apply to all acts of assisted suicide, those taking place within and outside of the jurisdiction.4 He then published an interim policy for wide consultation in September 2009, and is expected to produce the final policy in …